A global analysis of the seaward salt marsh extent: The importance of tidal range. Issue 5 (20th May 2016) - Balke, Thorsten; Stock, Martin; Jensen, Kai; Bouma, Tjeerd J.; Kleyer, Michael
Abstract: Despite the growing interest in ecosystem services provided by intertidal wetlands, we lack sufficient understanding of the processes that determine the seaward extent of salt marsh vegetation on tidal flats. With the present study, we aim to establish a globally valid demarcation between tidal flats and salt marsh vegetation in relation to tidal range. By comparing results from a regional GIS study with a global literature search on the salt marsh‐tidal flat border, we are able to define the global critical elevation, above which salt marsh plants can grow in the intertidal zone. Moreover, we calculate inundation characteristics from global tide gauge records to determine inundation duration and frequency at this predicted salt marsh‐tidal flat border depending on tidal range. Our study shows that the height difference between the lowest elevation of salt marsh pioneer vegetation and mean high water increases logarithmically with tidal range when including macrotidal salt marshes. Hence, the potentially vegetated section of the tidal frame below mean high water does not proportionally increase with tidal range. The data analysis suggests that inundation frequency rather than duration defines the global lower elevational limit of vascular salt marsh plants on tidal flats. This is critical information to better estimate sea level rise and coastal change effects on lateral marsh development. Key Points: A global analysis to establish the correlation between seaward salt marsh extent and tidal range Inundation frequency rather than duration defines the seaward limit of salt marsh vegetation Climate change studies on salt marshes should include tidal range